Análisis comparativo de tecnologías Flutter vs Swift en el modelo de procesos para el desarrollo de aplicaciones móviles. - Suarez García, Kasandra Thalía (2022)
Flutter and Swift at the moment are two of the most popular mobile app development solutions to date, for either of the two app development frameworks it can be difficult, due to the fact that the 2 are preferred for companies that would be creating applications for Android and iOS. The objective of this project is to carry out a comparative analysis between: Flutter vs. Swift, with this comparison, will allow us to detail each of its pros and cons when putting a mobile application into production, its features provided by both and the reason for its popularity. There are tools that are aimed at developing small projects and others that are more scalable, optimal and have a focus on business applications, but carrying out our mobile solutions with the help of a Framework can be due to several reasons, such as the Framework adapts to an established architecture, these tools constitute some libraries based on web components such as Flutter and Swift. Some are currently based on C++, they are used in the development of most applications and new tools are always appearing that seek to lead the market. To conclude this document about mobile development, more specifically in frameworks based on C++, I can say that the growth that these multiplatform technologies have had in recent years is great, because the tools delivered to the developer and their support community that works with them.